Cuda św. Menasa wg. bizantyńskiego synaksarionu z kodeksu New York, Harvard University, Houghton Library Typ 243H - Piotrowska, Katarzyna (Vox Patrum, 2025)
The presented text offers a Polish translation of the five miracles of St. Menas, as recorded in a Byzantine synaxarion composed in the 12th century. In the Introduction the circumstances of the collection’s composition are discussed and the key features of the recomposition of the miracles in comparison to their original Greek versions from the 5th–7th centuries are highlighted. The analysis focuses on the functions of the modifications and omissions, revealing the compiler’s deliberate choices influenced by local, historical, and cultural factors. The study examines both the collection as a whole and each miracle individually to identify common elements among all the translated texts, as well as those specific to particular narratives. The translation is accompanied by historical and linguistic commentary.